Persinggungan Kewenangan Penghitungan Kerugian Keuangan Negara dalam Tindak Pidana Korupsi Berdasarkan Peraturan Perundang-undangan dan Teori Beban Pembuktian: The Intersection of Authority to Calculate State Financial Losses in Criminal Acts of Corruption Based on Statutory Regulations and The Theory of Burden of Proof - Adhi, Murpraptono (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2025)
In cases of corruption, the occurrence of state financial losses is one of the elements that must be proven, as stipulated in Article 603 and Article 604 of Law Number 1 of 2023 concerning the Criminal Code (KUHP). According to the Explanation of Article 603 of the KUHP, the element of “causing a loss to state finances” is established based on the results of an audit conducted by a state financial auditing institution. This paper aims to analyze the intersection between the authority to calculate state financial losses regulated in the Criminal Code and the theory of burden of proof in criminal procedural law. This paper employs a normative legal method, utilizing both statutory and conceptual approaches. The findings indicate that the regulation of the authority to calculate state financial losses in the Criminal Code is inconsistent with the theory of burden of proof in criminal procedural law. This discrepancy leads to variations in how the party responsible for calculating state financial losses is identified in cases of corruption. According to the theory of burden of proof, it is the investigators and public prosecutors who bear the responsibility to prove the existence of state financial losses in corruption cases, not the state financial audit institution referenced in the Explanation of Article 603 KUHP.